Pelatihan Kerajinan Rajutan di Pondok Pesantren Darul Khuldi : Model Edukasi Kreatif bagi Santri di Desa Sri Mulya - Aura Putri Abelia; Destria Imelia; Astrina Utami; Tiara Jelita; Tiwany Arraya; Selvy Yuliani; Erni Sabela; Dwi Pratiwi; Puspita Devi (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
Knitting craft training at the Darul Khuldi Islamic Boarding School aims to increase the creativity and independence of students in Sri Mulya Village. This activity involved 36 students divided into six groups, where they learned basic knitting techniques and made knitted products that were of marketable value. The method used is participatory, with a direct approach through training sessions and discussions. The results of the training show that students are able to understand basic knitting techniques well, improve collaboration skills and creativity. Apart from that, this training also strengthens social ties between students and gives them confidence in creating products. Even though there are challenges in the availability of raw materials and learning time, it is hoped that this program can provide initial capital for students to develop handicraft skills and contribute to the development of the local economy.